Museum-based art activities to stay young at heart? Results of a randomized controlled trial - Cami, Margot; Planta, Océane; Matskiv, Jacqueline; Plonka, Alexandra; Gros, Auriane; Beauchet, Olivier (Frontiers in Medicine, 2024)
Background Health benefits have been reported with art activities. Heart rate is a biomarker of health state. The aim of this randomized controlled trial (RCT) was to compare the changes in heart rate over a 3 month-period in older adults participating in art-based activities at the Montreal Museum of Fine Arts (MMFA, Quebec, Canada) and in their control counterparts. Methods/design Participants (mean age 71.0 ± 5.1; 84.9% female) were a subset of older community dwellers recruited in a RCT in two parallel groups (n = 28 in the intervention group and n = 25 in the control group) who had their heart rate recorded. They attended weekly participatory MMFA-based art activities over a 3-month period. Heart rate was collected via the smart watch Fitbit Alta HR at baseline (M0) and at 3 months (M3). The outcomes were mean heart rate per hour for the full day, including active and inactive hours. Results Heart rate for full day (p = 0.018) and active hours (p = 0.028) were slower in the intervention group compared to the control group. Decrease in mean heart rate for full day between M0 and M3 in the intervention group was higher than in the control group (p = 0.030). The linear regression showed that MMFA-based art activities decreased full day heart rate (Coefficient of regression Beta = −6.2 with p = 0.010). Conclusion MMFA-based art activities significantly decreased full day heart rate, suggesting a health benefit in older community dwellers who participated in the RCT. Clinical trial registration: NCT03679715.